2018
DOI: 10.1016/j.jalgebra.2017.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Bounding Hilbert coefficients of parameter ideals

Abstract: Abstract. Let (R, m) be a Noetherian local ring of dimension d > 0 and depth R ≥ d − 1. Let Q be a parameter ideal of R. In this paper, we derive uniform lower and upper bounds for the Hilbert coefficient ei(Q) under certain assumptions on the depth of associated graded ringFurther, we obtain a necessary condition for the vanishing of the last coefficient e d (Q). As a consequence, we characterize the vanishing of e2(Q

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…This implies that if d = 4, depth(A) ≥ 3 and σ(Q) ≥ 2, then e i (Q) ≤ 0 for i = 1, 2, 3, 4. From Proposition 3.5, it follows an early result of Saikia-Saloni [20] and Linh-Trung [13]. As a consequence, it follows that if d ≥ 3 and depth(A) ≥ d − 1, then e i (Q) ≤ 0 for i = 1, 2, 3.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…This implies that if d = 4, depth(A) ≥ 3 and σ(Q) ≥ 2, then e i (Q) ≤ 0 for i = 1, 2, 3, 4. From Proposition 3.5, it follows an early result of Saikia-Saloni [20] and Linh-Trung [13]. As a consequence, it follows that if d ≥ 3 and depth(A) ≥ d − 1, then e i (Q) ≤ 0 for i = 1, 2, 3.…”
Section: Introductionmentioning
confidence: 58%
“…However, if depth(A) ≥ d − 1, McCune [16] showed that e 2 (Q) ≤ 0 for every parameter ideal Q. In [20], Saikia and Saloni proved that if depth(A) ≥ d − 1, then e 3 (Q) ≤ 0 for every parameter ideal Q. In [16], McCune also proved that if Q is a parameter ideal such that depth(G(Q)) ≥ d − 1, then e i (Q) ≤ 0 for i = 1, .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…showed that 2 ( ) ≤ 0 and Saikia-Saloni [3] proved that 3 ( ) ≤ 0 for every parameter ideal . Recently, Linh-Trung [4] proved that if ℎ( ) ≥ − 1 and is a parameter ideal such that ℎ( ( )) ≥ − 2 , then ( ) ≤ 0 for = 1, … , .…”
Section: Introductionmentioning
confidence: 98%
“…We obtain that e 3 (I) ≤ 0 if e 2 (I) ≤ 2 and e 3 (I) ≤ 2 if e 2 (I) = 3. Discussions on the signature and vanishing of Hilbert coefficients can be found in [2], [3], [6], [7], [14], [17], [19], [28] etc. Suppose depth G(I) ≥ d − 1.…”
Section: Introductionmentioning
confidence: 99%